The influence of creatine on brain functioning - Lewandowska, Dominika; Katarzyna Otrębska; Aleksandra Makulec; Natalia Kostecka; Aleksandra Jóźwik-Szymańska; Laura Mikuła; Aleksandra Szredzka; Zuzanna Bogdan-Groszyk; Kucharski, Jan (Quality in Sport, 2026)
Creatine is a key component of cellular energy metabolism, supporting ATP resynthesis. Increasing attention has been given to its potential effects on brain function, including cognition, mood regulation, and neuroprotection. The aim of this review was to summarize current evidence on the effects of creatine supplementation on brain function, with a focus on cognitive performance, neurodegenerative diseases, and affective disorders. The literature review included randomized controlled trials, clinical and observational studies, as well as experimental research identified in major scientific databases. Creatine acts primarily by enhancing cellular bioenergetics, increasing ATP availability, and supporting mitochondrial function. The evidence suggests modest cognitive benefits, particularly improvements in memory and processing speed, especially under conditions of increased metabolic demand, such as sleep deprivation or cognitive fatigue. In neurodegenerative diseases, findings remain inconsistent—despite promising preclinical data, large clinical trials have not demonstrated significant therapeutic effects. In affective disorders, particularly depression, creatine shows potential as an adjunctive treatment, enhancing the effectiveness of standard therapies. However, in bipolar disorder, supplementation may carry a risk of triggering manic or hypomanic episodes. Overall, creatine supplementation is a biologically plausible, generally safe, and well-tolerated intervention with context-dependent effects on brain function. While it may provide modest cognitive benefits and support the treatment of depression, current evidence does not justify its use as a primary therapy for neurodegenerative diseases. Further large-scale, well-designed studies are needed to clarify its clinical utility in neuropsychiatric conditions.